George Du Maurier, the Satirist of the Victorians - Wood, T. Martin, 1875-1919 (Salt Lake City, UT : Project Gutenberg, 2004)
"George Du Maurier, the Satirist of the Victorians" by T. Martin Wood is a historical account written during the early 20th century. The book aims to provide a comprehensive exploration of the life and artistic accomplishments of George Du Maurier, particularly focusing on his role as a satirist through his illustrations and writings in the Victorian era. It reflects on his artistic influence, the social dynamics of the time, and how he mirrored Victorian society in his work. The opening of this work introduces the premise of exploring Du Maurier$1 (Bs contributions to Victorian satire through his drawings and writings, primarily as featured in the magazine "Punch". It discusses the artist$1 (Bs perspective on social norms and transformations during his time, illustrating how he commented on the evolving role of class and civility in society. The text highlights Du Maurier$1 (Bs skill in depicting social interactions and the essence of drawing-room life, emphasizing the interplay between humor and critique in his art. The author sets the stage for analyzing Du Maurier$1 (Bs artistic style and legacy, underlining both the depth and charm of his engagement with the complexities of Victorian culture. (This is an automatically generated summary.)s
Release date is 2004-12-20
E-text prepared by Jonathan Ingram, Susan Skinner, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Du Maurier, George, 1834-1896